The Effect of Compensation, Work Life Balance and Employee Well-Being on Turnover Intention at PT AAA - Chusniah Chusniah; Ratri Wahyuningtyas (International Journal Labs, 2025)
The competitive aviation industry challenges companies like PT AAA, a low-cost carrier in Indonesia, to retain loyal and stable human resources. Recently, PT AAA has faced rising employee turnover, which threatens productivity and organizational effectiveness. Key contributing factors include dissatisfaction with compensation, poor work-life balance, and declining employee well-being. This study aims to examine the influence of compensation, work-life balance, and employee well-being on turnover intention. Using a quantitative approach with 330 respondents comprising ground staff, pilots, and cabin crew data were collected via questionnaires and analyzed using SEM-PLS. The findings show that compensation (t = 7.143), work-life balance (t = 5.745), and employee well-being (t = 6.276) each have a significant negative effect on turnover intention (p < 0.05). The model’s R² value is 0.477, indicating that 47.7% of the variance in turnover intention is explained by these three variables. The study concludes that PT AAA should consistently improve its compensation structures, promote better work-life balance, and enhance employee well-being programs to reduce turnover and support sustainable organizational performance.